2014
DOI: 10.1111/jace.13135
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Compositional Homogeneity in Pb(Zr,Ti)O3 Using Atom Probe Tomography

Abstract: Atom probe tomography (APT) is a powerful materials characterization technique capable of ppm chemical resolution and near atomic scale spatial resolution. However, owing to a number of factors, the technique has not been widely applied to insulating materials and even less to complex oxides. In this study, we outline the methodology necessary to obtain high‐quality results on a technologically relevant complex oxide Pb(Zr,Ti)O3 (or PZT) using laser‐assisted APT on both bulk and thin film specimens. We show ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 74 publications
1
32
1
Order By: Relevance
“…7) is ascribed to a two-mode behavior of Na-and K-based chemical clusters, 28 and thus is influenced by A-site doping. Experimental confirmation of chemical clusters in ferroelectrics was performed very recently, 71 in agreement with the described two-mode behavior. Also, the Ti-O mode at $270 cm À1 and the higher wavenumber (oxygen-related) modes can be influenced by chemical substitution, because replacement of a cation with different size at the A-site produces distortion of the unit cell.…”
supporting
confidence: 74%
“…7) is ascribed to a two-mode behavior of Na-and K-based chemical clusters, 28 and thus is influenced by A-site doping. Experimental confirmation of chemical clusters in ferroelectrics was performed very recently, 71 in agreement with the described two-mode behavior. Also, the Ti-O mode at $270 cm À1 and the higher wavenumber (oxygen-related) modes can be influenced by chemical substitution, because replacement of a cation with different size at the A-site produces distortion of the unit cell.…”
supporting
confidence: 74%
“…In geological materials, there is typically a lower O composition than would be predicted from mineral stoichiometry and it is notable that molecular dissociation in O‐rich phases has been suggested to be related to the possible formation of neutral O 2 during dissociation (Karahka and Kreuzer ; ; Silaeva et al ). It has also been suggested that the temperature increase associated with the interaction between the laser and the atom probe specimen can favour the thermal desorption of neutral gaseous molecules, such as N 2 and O 2 , from the specimen (Riley et al , Devaraj et al , Kirchhofer et al ) and this will also potentially affect mineral stoichiometry.…”
Section: Technique Limitations Analysis Artefacts and Potential Solumentioning
confidence: 99%
“…174 There have also been other mechanisms proposed in order to rationalize the extrinsic contributions to the electromechanical enhancement around MPBs. For instance, chemical ordering 181,182 , formation of nanodomains 174,183,184 with facilitated switching 185 , and others have been invoked. However, even in the case of domain miniaturization, it has been pointed out that the most important factor to consider is the mobility of domains rather than their size.…”
Section: Electromechanical Enhancements In Ferroelectricsmentioning
confidence: 99%